Gardnerella vaginalis as a Cause of Abscesses and Bacteremias: A Narrative Review Apropos of a Clinical Case. Issue 5 (September 2017) - Macedo-Viñas, Marina; Petitpierre, Nicolas; Cherkaoui, Abdessalam; Wirth, Gregory; Kaiser, Laurent
Abstract : Abstract: Gardnerella vaginalis is infrequently reported as a cause of extragenital infections. Although the pathogenesis of G. vaginalis is not completely understood, available clinical data suggest that it is an opportunistic pathogen that can cause invasive infections. We report a case of pyelonephritis imputed to G. vaginalis, with renal abscess and bacteremia in a diabetic nonpregnant woman with polycystic kidney disease. Gardnerella vaginalis was isolated from blood, the abscess, and urine obtained by direct placement of a pigtail into the kidney. Identification was made with molecular methods. We present a review of the literature concerning G. vaginalis extragenital infections, with special focus on abscesses and bacteremias. We searched PubMed for articles in English, French, German, and Spanish languages. Only 15 cases of abscesses from diverse body sites have been reported. We found 28 articles describing a total of 117 cases of bacteremia. Most of them occurred in women in the peripartum periods and in newborns. Cases in men have been described with lower frequency. The importance of this agent might be underestimated because microbiological diagnosis is difficult. Most cases in adults were nonfatal and without sequelae. There is no consensus on the antibiotic regimen and duration of treatment for these infections. New microbiological diagnosis tools may lead to prompt identification of this microorganism and help to elucidate its participation in localized and systemic infections. Abstract : Gardnerella vaginalis extra-vaginal infections are seldom reported. A complex clinical case of pyelonephritis imputed to G. vaginalis, with renal abscess and bacteremia in a diabetic non-pregnant woman with polycystic kidney disease is presented. An exhaustive review of the published literature on this topic is presented.